Open-label tofacitinib and double-blind atorvastatin in rheumatoid arthritis patients: a randomised study - McInnes, Iain B; Kim, Ho-Youn; Lee, Sang-Heon; Mandel, David; Song, Yeong-Wook; Connell, Carol A; Luo, Zhen; Brosnan, M Julia; Zuckerman, Andrea; Zwillich, Samuel H; Bradley, John D (Annals of the rheumatic diseases, 2014)
Objectives To evaluate the efficacy and safety of atorvastatin versus placebo in modifying lipids in patients with rheumatoid arthritis (RA) receiving the oral Janus kinase inhibitor, tofacitinib. Methods A randomised, placebo controlled, multicentre phase 2 study, open-label for tofacitinib and blinded for atorvastatin. Patients received tofacitinib 10 mg twice daily for 12 weeks; at week 6, patients were randomly assigned 1:1 to receive oral atorvastatin 10 mg once daily or placebo for 6 weeks. Main outcome measures were lipid moieties, American College of Rheumatology (ACR) response rates, disease activity score in 28 joint counts and safety. Results 111 patients meeting ACR 1987 RA criteria with active disease were enrolled. Tofacitinib-induced elevation of mean total, low-density lipoprotein (LDL) and high-density lipoprotein-cholesterol, triglycerides and apolipoprotein A-1 concentrations were sustained in placebo recipients to week 12; atorvastatin added at week 6 significantly reduced tofacitinib-associated increases in total and LDL-cholesterol, triglycerides and apolipoprotein B to below week 0 levels. Co-administration of atorvastatin resulted in a significant reduction of LDL-cholesterol versus placebo (primary endpoint; p<0.0001); from week 6 to week 12 the least squares mean reduction was 35.3% with atorvastatin, versus 5.8% increase with placebo. ACR responses were observed with tofacitinib; numerically greater rates were seen with atorvastatin versus placebo. Adverse events were consistent with phase 3 studies. Conclusions Tofacitinib-associated elevated total and LDL-cholesterol and triglycerides were rapidly and significantly reduced by atorvastatin. Further investigation is required to explore the significance of reductions in RA disease activity in patients receiving tofacitinib and atorvastatin. (http://www.ClinicalTrials.gov identifier NCT01059864; Pfizer protocol A3921109).